Numerical characterization of hemodynamics conditions near aortic valve after implantation of left ventricular assist device - Annalisa Quaini; Sunčica Čanić; David Paniagua (Mathematical Biosciences and Engineering)
Left Ventricular Assist Devices (LVADs) are implantable mechanical pumps that temporarily aid the function of theleft ventricle. The use of LVADs has been associated with thrombus formation next to the aortic valve and close to the anastomosis region,especially in patients in which the native cardiac function isnegligible and the aortic valve remains closed.Stagnation points and recirculation zones have been implicated as the main fluid dynamics factors contributing to thrombus formation.The purpose of the present study was to develop and use computer simulations based on afluid-structure interaction (FSI) solver to study flow conditions corresponding to different strategies inLVAD ascending aortic anastomosis providing a scenario with the lowest likelihood of thrombus formation.A novel FSI algorithm was developed to dealwith the presence of multiple structures corresponding to different elastic properties ofthe native aorta and of the LVAD cannula.A sensitivity analysis of different variables was performed to assess their impact of flow conditionspotentially leading to thrombus formation.It was found that the location of the anastomosis closest to the aortic valve(within 4 cm away from the valve)and at the angle of 30$^°$ minimizes the likelihood of thrombus formation.Furthermore, it was shownthat the rigidity of the dacron anastomosis cannula plays almost no role in generating pathologicalconditions downstream from the anastomosis.Additionally, the flow analysis presented in this manuscriptindicates that compliance of the cardiovascular tissue acts as a natural inhibitor of pathological flow conditions conducive to thrombus formationand should not be neglected in computer simulations.